Anti-phosphohistone H3 (PHH3) as a proliferation marker to assess mitotic activity and to grade neuroendocrine neoplasms of hepatopancreaticobiliary (HPB) system - A Prisca Santhanam; Anjana Joel; Anoop Paul; Uday G. Zachariah; Grace J. Rebekah; Thomas A. Kodiatte (Indian Journal of Pathology and Microbiology)
Background: The world health organization (WHO) classification of neuroendocrine neoplasms (NENs, i.e. neuroendocrine tumors (NETs) and neuroendocrine carcinomas (NECs)) of the gastrointestinal system involves grading of these tumors by mitotic count (i.e. H and E mitotic index or Haematoxylin and Eosin mitotic index [HE-MI] and Mindbomb E3 ubiquitin protein ligase 1 labelling index (MIB1-LI) into Grade 1 (G1), Grade 2 (G2), or Grade 3 (G3). However, the assessment of HE-MI and MIB1-LI is hindered by several factors that contribute to discordance between these two grading methods. Clinical data demonstrate the dependency of prognosis on grade. Objectives: The objective of this study was to compare the grading of NENs of the hepatopancreatobiliary (HPB) system using Anti-phosphohistone H3 mitotic index (i.e. PHH3-MI), HE-MI and MIB1-LI. Materials and Methods: In a cohort of 140 NENs selected from January 2011 to August 2019, the concordance and correlation between HE-MI, MIB1-LI and PHH3-MI grading methods were analysed using Cohen’s weighted kappa (κ) statistics and Spearman’s correlation (ρ), respectively. Receiver operating characteristic (ROC) curve and cut-off analyses were done to determine optimal PHH3-MI cut-off values to grade NENs. Results: The rates of discordance between HE-MI vs. MIB1-LI, PHH3-MI vs. MIB1-LI and PHH3-MI vs. HE-MI were 52% (κ =0.416), 29% (κ =0.64) and 41% (κ =0.508), respectively. There was a significant correlation between the grading methods. PHH3-MI had good overall sensitivity and specificity at cut-offs 2 and 17 in distinguishing between G1 vs. G2, and G2 vs. G3 tumors, respectively. Conclusion: PHH3 immunolabeling allowed for quick and easy identification of mitotic figures (MF). It had the highest concordance with MIB1-LI. At cut-off values of 2 and 17, there was good overall sensitivity and specificity. The interobserver agreement was excellent.